2014
DOI: 10.1039/c4pp00117f
|View full text |Cite
|
Sign up to set email alerts
|

Partial charge transfer contribution to the solvent isotope effect and photosensitized generation of singlet oxygen, O2(1Δg), by substituted ruthenium(ii) bipyridyl complexes in aqueous media

Abstract: The efficiency of singlet oxygen photosensitized by some ruthenium(ii) bipyridyl complex ions in aqueous media is reported in this study. Measurements were carried out in H2O and D2O. The effect of the deuterium isotope on the lifetime of (3)MLCT excited states of these complexes is studied in H2O and D2O. The deuterium isotope effect was discussed in terms of the vibronic coupling to the solvent in addition to the charge transfer to the solvent mechanism due to their dependence on the oxidation potential of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Singlet oxygen ( 1 O 2 , 1 D g ), the lowest excited state of the dioxygen molecule, can be generated by photochemical and chemical processes [1][2][3][4][5][6]. The most common photochemical method involves energy transfer from a triplet excited photosensitizer ( 3 *PS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singlet oxygen ( 1 O 2 , 1 D g ), the lowest excited state of the dioxygen molecule, can be generated by photochemical and chemical processes [1][2][3][4][5][6]. The most common photochemical method involves energy transfer from a triplet excited photosensitizer ( 3 *PS).…”
Section: Introductionmentioning
confidence: 99%
“…The most common photochemical method involves energy transfer from a triplet excited photosensitizer ( 3 *PS). Many dyes, including some diimides [2][3][4] and metal complexes [3][4][5][6][7][8][9][10] can be used as photosensitizers for the production of 1…”
Section: Introductionmentioning
confidence: 99%
“…We studied the mechanism of the photocatalytic aerobic THF oxidation. Singlet oxygen was first ruled out as the oxidant, since Ru(bpy) 3 2+ , which is known to generate singlet oxygen, did not oxidize THF under the photocatalytic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…This is because of the relatively long lifetime of the triplet metal-to-ligand charge transfer states, 3 MLCT, of many Ru(II) coordination compounds that make these excited states susceptible to quenching by oxygen. It is been reported that the MLCT absorption mainly produces 1 MLCT that undergo ISC and populate 3 MLCT [127]. …”
Section: Increased 1o2 Productionmentioning
confidence: 99%